Nutritive value of forages as affected by soil and climatic differences - Richardson, D.; Banbury, Evans E.; Erhart, A.B.; Williams, G.; Russ, Oliver G.; Harbers, L.H.; Loper, D.C.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
This is a progress report on the second test to determine whether there is a differences in the performance of beef steers due to location, soil, climate, rainfall and/or feed produced in four area of Kansas: Colby, Garden City, Manhattan, and Mound Valley. Forty-eight Hereford steer calves averaging 454 pounds each were divided into four groups of 12. One lot was assigned to each location. Sorghum silage from the same variety (FSIA) and second cutting of alfalfa plus plain salt were used in the wintering phase. Feedstuff analyses are show in Table 36, and results of the wintering phase, in Table 35. Silage has been removed from the ration and sorghum grain added. The animals will be fattened for slaughter.
Keywords: Beef; Performance; Sorghum grain; Alfalfa